2022
DOI: 10.1038/s41598-022-14881-9
|View full text |Cite
|
Sign up to set email alerts
|

A laser parameter study on enhancing proton generation from microtube foil targets

Abstract: The interaction of an intense laser with a solid foil target can drive $$\sim$$ ∼ TV/m electric fields, accelerating ions to MeV energies. In this study, we experimentally observe that structured targets can dramatically enhance proton acceleration in the target normal sheath acceleration regime. At the Texas Petawatt Laser facility, we compared proton acceleration from a $$1\, {\upmu }\hbox {m}$$ 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Very recently, high-yield and high-energy ion generation by using thin foil targets with evenly spaced holes was performed. 32 In such an experiment, a 3D printer was used to place thin foils with holes at equal intervals on the surface of a solid plane target. They observed that the conversion efficiency from the laser beam to energetic electrons (Ee > 100 keV) enhanced to more than 50% at a laser intensity of 4 × 10 20 W/cm 2 by using such a target.…”
Section: Articlementioning
confidence: 99%
“…Very recently, high-yield and high-energy ion generation by using thin foil targets with evenly spaced holes was performed. 32 In such an experiment, a 3D printer was used to place thin foils with holes at equal intervals on the surface of a solid plane target. They observed that the conversion efficiency from the laser beam to energetic electrons (Ee > 100 keV) enhanced to more than 50% at a laser intensity of 4 × 10 20 W/cm 2 by using such a target.…”
Section: Articlementioning
confidence: 99%